Effect of Methyl, Hydroxyl, and Chloro Substituents in Position 3 of 3′, 4′, 7‐Trihydroxyflavylium: Stability, Kinetics, and Thermodynamics. Issue 35 (28th July 2016) - Alejo‐Armijo, Alfonso; Salido, Sofía; Altarejos, Joaquín; Parola, A. Jorge; Gago, Sandra; Basílio, Nuno; Cabrita, Luis; Pina, Fernando
Abstract: The effect of methyl, hydroxyl, and chloride substituents in position 3 of the 3′, 4′, 7‐trihydroxyflavylium core structure was studied. The stability, relative energy of each of chemical species (thermodynamics), and their rates of interconversion (kinetics) are very dependent on these substituents. By comparing the mole fraction distribution at equilibrium of the three multistate systems with the parent 3′, 4′, 7‐trihydroxyflavylium, introduction of a methyl substituent in position 3 increases the mole fraction of hemiketal at the expense of the trans ‐chalcone and increases the hydration rate very significantly; a hydroxyl substituent in position 3 gives rise to a degradation process, as observed in anthocyanidins. In the case of 3‐chloro‐3′, 4′, 7‐trihydroxyflavylium, a dramatic increase of the flavylium cation acidity was observed and a photochromic system can be operated upon irradiation of the respective trans ‐chalcone in 1 m HCl. According to the photochromic response of 3, 3′, 4′, 7‐tetrahydroxyflavylium and 3′, 4′, 7‐trihydroxyflavylium, some requirements for a good photochromic performance are discussed. Abstract : Photochromism in 1 m HCl : Changing the substituent in position 3 of the flavylium core structure leads to dramatic changes to the thermodynamics and kinetics of the multistate molecular network (see figure). In the case of chlorine, the photochromic system operates under extremely acidic conditions.